IMPACT OF MINIMUM WAGE ON UNEMPLOYMENT AND WORKER WELFARE VIA ECONOMIC GROWTH IN WEST JAVA (2010-2021) - Audit, Abib; Kadarwati, Nunik; Binardjo, Goro (Jurnal Ilmu Ekonomi dan Pembangunan, 2024)
This study examines the impact of minimum wage policies on unemployment and worker welfare in West Java from 2010 to 2021, with a particular focus on the role of economic growth as a mediating variable. Utilizing a time series econometric approach, we analyze data from various economic indicators to understand the dynamics between these variables. The findings indicate that while minimum wage increases are associated with a reduction in unemployment, the effect is significantly mediated by economic growth, which also enhances worker welfare. This study contributes to the literature by providing empirical evidence from a developing country context and offering practical insights for policymakers aiming to balance wage growth with employment and economic stability.